Little shop of horrors (1986) [videorecording (DVD)] - Ashman, Howard; Oz, Frank; Moranis, Rick; Greene, Ellen; Gardenia, Vincent; Martin, Steve, 1945-; Belushi, James, 1954-; Candy, John; Guest, Christopher; Murray, Bill, 1950 September 21- (Warner Home Video, 2000)
In this musical, business booms at Mushnik's Flower Shop when an exotic potted plant called Audrey II arrives. People are rushing in to see it--and disappearing.